LITERATURE REVIEW FACTORS AFFECTING CRITICAL THINKING: CURRICULUM, STUDENTS, AND EDUCATIONAL FACILITIES - Muhammad Rifai; Kemas Imron Rosadi (Dinasti International Journal of Education Management And Social Science, 2022)
Islam highly upholds education, even the first revelation that was revealed was the command to read, from reading humans can gain knowledge and know many things. The Prophet sallallaahu 'alaihi wasallam in many of his hadiths, he obliges his people to always learn. Islamic education has a very noble goal, namely making humans able to carry out Islamic law properly and correctly. To achieve this goal, of course, it is not as easy as we imagine, but good management is needed in the administration of education, including by thinking critically on the curriculum, students, and educational facilities. Thus, it is hoped that Islamic education in Indonesia in the future can be of higher quality. This paper attempts to analyze critical thinking on the curriculum, students, and means of education.